ELASTISITAS JUMLAH TABUNGAN TERHADAP SISA HASIL USAHA PADA KUD SUMBER MAKMUR KECAMATAN TANJUNG KABUPATEN BREBES - Rahayu, Sri (PERMANA, 2014)
Elasticity storey;level of[is amount of saving to highest SHU in the year 2008 that is equal to 34,40% while lowered in the year 2009 that is - 32,64% ( reaching the condition of inelastis). So that as a whole if seen from mean can be expressed that storey;level sensitivity of saving amount to net income not yet elastic ( inelastis).